Analytic Network Process and Tawhidi String Relation in Managing Business of Sharia Commercial Bank - Praptiwi Lestiyawati (Aptisi Transactions On Technopreneurship (ATT), 2023)
Islamic banking is a multiple microfinance management business concept. By determining solutions and examining their methods for present and future microfinance management, the Kema Logical Organization Cycle and Tawhidi String Relationship technique seeks to identify any problems or restrictions in existing financial conditions. Islamic banks employ techniques including Super Choice program support and Insightful Organization Interaction. The Analytic Network Process approach and Super Decision software support are used in this study. The purposive sampling approach will be used to pick a number of participants for this research, including practitioners, academics, specialists, and regulators.Based on the results of this research, BTPNS, the only bank that provides the finest services, focuses on the income earners of productive low-income groups and places a priority on the empowerment of women. BTPNS also creates training programs to help people develop skills, discipline, and hard work in order to boost the community's economy. Providing MSME training; The partnership between BRIS and BNIS provides benefits in infrastructure development and long-term financial management. Implementing the funds offered by Islamic banks has as its goal enhancing management and microfinance in order to develop an Islamic retail bank with such a business model that prioritizes welfare.